Returning to the Fold for Lessons in Mitochondrial Crista Diversity and Evolution - Pánek, Tomáš; Eliáš, Marek; Vancová, Marie; Lukeš, Julius; Hashimi, Hassan (Current biology, 2020)
Cristae are infoldings of the mitochondrial inner membrane jutting into the organelle's innermost compartment from narrow stems at their base called crista junctions. They are emblematic of aerobic mitochondria, being the fabric for the molecular machinery driving cellular respiration. Electron microscopy revealed that diverse eukaryotes possess cristae of different shapes. Yet, crista diversity has not been systematically examined in light of our current knowledge about eukaryotic evolution. Since crista form and function are intricately linked, we take a holistic view of factors that may underlie both crista diversity and the adherence of cristae to a recognizable form. Based on electron micrographs of 226 species from all major lineages, we propose a rational crista classification system that postulates cristae as variations of two general morphotypes: flat and tubulo-vesicular. The latter is most prevalent and likely ancestral, but both morphotypes are found interspersed throughout the eukaryotic tree. In contrast, crista junctions are remarkably conserved, supporting their proposed role as diffusion barriers that sequester cristae contents. Since cardiolipin, ATP synthase dimers, the MICOS complex, and dynamin-like Opa1/Mgm1 are known to be involved in shaping cristae, we examined their variation in the context of crista diversity. Moreover, we have identified both commonalities and differences that may collectively be manifested as diverse variations of crista form and function.
Keywords: Biodiversity; Eukaryota; druhová specificita; biodiverzita; mitochondriální membrány; Mitochondria; biologická evoluce; Mitochondrial Membranes; Biological Evolution; mitochondrie; Species Specificity